Measuring the Quality of Life in Forensic Psychiatric Hospitals - Büsselmann, Michael; Titze, Larissa; Lutz, Maximilian; Dudeck, Manuela; Streb, Judith (Frontiers in Psychology, 2021)
Background: In Germany, a large proportion of mentally ill offenders spends many years in a forensic psychiatric hospital. To ensure that the highly restrictive living conditions in these closed institutions meet patient needs, research must assess and analyze patient quality of life. For this purpose, we adapted the Measuring the Quality of Prison Life questionnaire to measure the quality of life in forensic psychiatric hospitals from the patient perspective. This study aimed to assess the reliability (internal consistency) and construct validity of the adapted questionnaire. Methods: To evaluate the questionnaire, a one-time survey was carried out at 13 forensic psychiatric hospitals in Germany. Item characteristics and internal consistency of the scale and subscales were calculated and the factor structure was tested using confirmatory factor analysis. To test of responsiveness we compared the mean quality of life between the 13 hospitals and further investigated whether the patients' evaluation of quality of life is depending on age and duration of accommodation. Results: The analysis of the psychometric properties revealed very good item characteristics and very good to excellent internal reliability. Construct validity was demonstrated. Patient's quality of life was significantly associated with age and duration of accommodation. Discussion: The adapted Measuring the Quality of Prison Life questionnaire is a reliable and valid instrument for measuring quality of life in forensic psychiatric hospitals and can be used in the future to compare hospitals and identify the strengths and weaknesses of each.